Efficacy of Coxsackievirus A2 vaccine candidates correlating to humoral immunity in mice challenged with a mouse-adapted strain. Issue 33 (5th August 2022) - Hu, Gang; Jin, Wei-Ping; Yang, Zhi-Hui; Lv, Shi-Yun; Wu, Jie; Yu, Yu-Ting; Meng, Sheng-Li; Guo, Jing; Wang, Ze-Jun; Shen, Shuo
Abstract: Background: In recent years, Coxsackievirus A2 (CV-A2) has become one of the main serotypes of enterovirus species A associated with hand, foot and mouth disease (HFMD) in China. It has also caused HFMD epidemics in many countries all over the world. Currently, there are no effective, preventive vaccines against it. Methods: A CV-A2 strain was isolated in RD cells and then adapted to grow in Vero cells. This is in compliance with guidelines for cell substrates allowed for human vaccines by the Chinese regulatory authority. Groups of newborn Kunming mice were inoculated on day 3 and day 9 using two formulations of candidate vaccines, empty particles and full particles. They were then challenged on day 14 at a lethal dose with a mouse-adapted strain. Results: The mice in the control group all died within 14 days post-challenge whereas most of the mice in the candidate vaccine groups survived. It was found that the titers of neutralizing antibodies was dose-dependent in sera of immunized mice. The results also showed that the vaccine candidates stimulated a strong humoral immune response and protected the mice from disease and death. The virus loads in tissues or organs were significantly reduced and pathological changes were either weak or not observed in the immunized groups compared with those in Al(OH)3 control group. Preliminary mapping of the nucleotide and amino acid residues potentially related to cell tropism of the vaccine strain and virulence of the challenge strain was performed. Conclusion: The results showed that the RD cell-isolated and Vero cell-adapted CV-A2 strain is a promising vaccine candidate. This active immunization-challenge mouse model mimics the vaccination and then exposure to wildtype viruses, compared with passive immunization-challenge model, and is invaluable for efficacy evaluation in studies on multivalent vaccines containing CV-A2 against HFMD.